Priority Analysis of Mangrove Guraping Ecotourism Development Based on Spatial Data Using Process Hierarchy Analysis - Yerik Afrianto Singgalen (Universitas Bina Darma, 2022)
This article aims to analyze the development priorities of Guraping mangrove ecotourism based on spatial data using process hierarchy analysis (AHP). The research process is divided into three stages: the pre-processing stage, processing stage, analyzing and reporting phase. In the processing stage, the spatial data used is Landsat 8 OLI in the Guraping mangrove ecotourism area from 2013-2021 with the Coordinate Reference System World Geodetic System (WGS) 84 or Universal Transverse Mercator (UTM) Zone 52N. In the Processing stage, raster data for each zone in the Guraping mangrove ecotourism area will be calculated using the Normalized Difference Vegetation Index (NDVI) algorithm to determine the maximum, average, and minimum values value. The analyzing and reporting phase contains an idea of NDVI calculations result related to the Decree of the Minister of State for the environment in 2004. The findings of this study indicate that the ranking system in the Analytical Hierarchy Process (AHP) algorithm can be used to analyze the priority of the Guraping mangrove ecotourism development program. In AHP Calculation, the programs consist of rehabilitation, restoration, reclamation, and conservation. In addition, the alternatives are zone 1, zone 2, and zone 3. The ranking results show that the program relevant to the NDVI calculation of the Guraping mangrove ecotourism context is the rehabilitation program. Furthermore, the alternative ranking results show that Zone 1 is the priority zone for the rehabilitation program.